Cohort Randomised Controlled Trial of a Multifaceted Podiatry Intervention for the Prevention of Falls in Older People (The REFORM Trial). - Sarah Cockayne; Joy Adamson; Arabella Clarke; Belen Corbacho; Caroline Fairhurst; Lorraine Green; Catherine E Hewitt; Kate Hicks; Anne-Maree Kenan; Sarah E Lamb; Caroline McIntosh; Hylton B Menz; et al. (PLoS ONE)
Background Falls are a major cause of morbidity among older people. A multifaceted podiatry intervention may reduce the risk of falling. This study evaluated such an intervention. Design Pragmatic cohort randomised controlled trial in England and Ireland. 1010 participants were randomised (493 to the Intervention group and 517 to Usual Care) to either: a podiatry intervention, including foot and ankle exercises, foot orthoses and, if required, new footwear, and a falls prevention leaflet or usual podiatry treatment plus a falls prevention leaflet. The primary outcome was the incidence rate of self-reported falls per participant in the 12 months following randomisation. Secondary outcomes included: proportion of fallers and those reporting multiple falls, time to first fall, fear of falling, Frenchay Activities Index, Geriatric Depression Scale, foot pain, health related quality of life, and cost-effectiveness. Results In the primary analysis were 484 (98.2%) intervention and 507 (98.1%) control participants. There was a small, non statistically significant reduction in the incidence rate of falls in the intervention group (adjusted incidence rate ratio 0.88, 95% CI 0.73 to 1.05, p = 0.16). The proportion of participants experiencing a fall was lower (49.7 vs 54.9%, adjusted odds ratio 0.78, 95% CI 0.60 to 1.00, p = 0.05) as was the proportion experiencing two or more falls (27.6% vs 34.6%, adjusted odds ratio 0.69, 95% CI 0.52 to 0.90, p = 0.01). There was an increase (p = 0.02) in foot pain for the intervention group. There were no statistically significant differences in other outcomes. The intervention was more costly but marginally more beneficial in terms of health-related quality of life (mean quality adjusted life year (QALY) difference 0.0129, 95% CI -0.0050 to 0.0314) and had a 65% probability of being cost-effective at a threshold of £30,000 per QALY gained. Conclusion There was a small reduction in falls. The intervention may be cost-effective. Trial registration ISRCTN ISRCTN68240461.